A novel nanofiltration membrane with a sacrificial chlorine-resistant nanofilm: design and characterization of tailored membrane pores and surface charge - Tian, Miao (2022)
Nanofiltration (NF) membranes are important for the resource of the wastewater from the coal chemical industry, brackish water and seawater desalination, and other purification applications to overcome the shortage of fresh water. However, ordinary NF membranes are easily oxidized by the residual chlorine in the influent. Here, we report a phase transition of lysozyme nanofilm for tuning the nanopore and surface charge of commercial NF membranes by a one-step dip-coating method using a buffer solution mixed with lysozyme. The pore size and selectivity of the membrane can be tailored through the coating time. The nanofilm can protect the membrane as a sacrifice layer from the corrosion of sodium hypochlorite solution. X-ray photoelectron spectroscopy (XPS) results confirmed that the nanofilm disappeared after being oxidized by 1000 ppm NaClO for 30 h. Nanofilm can effectively keep the rejection rate of Na2SO4 at ~96 %. Our work proves the potential use of nanofilm as a good post-treatment for regulating membrane pore structure and surface charge. The construction of the sacrificial layer, which has also been proven to be universal for other types of membranes, provides a new idea for the NF membrane to resist sodium hypochlorite oxidation.